Study of Serum PSA, AMACR, P63 And PTEN in Prostatic Adenocarcinoma - Sengupta, Prashant; Taur, Nishant; Ranjan, Richa; Vardhan, Rig (Annals of Pathology and Laboratory Medicine, 2019)
Background: Prostatic adenocarcinoma is the most common malignancy in older males. The present study was planned with an aim to evaluate serum PSA, expression of P63, AMACR and PTEN in prostatic carcinoma and to correlate them clinico-pathologically. It is a descriptive analytical study which includes patients of prostatic adenocarcinoma reporting to a large tertiary care hospital in Lucknow during the period of 2015-to 2017. Methods: Clinical details and complete hematological workup was done in 50 cases of prostatic adenocarcinoma during our study period of two years. Routine histopathology with hematoxylin and eosin (H & E) staining was done. Gleason grading was performed. Relevant sections were taken for Immunohistochemistry (IHC) to study PTEN, AMACR and P63. Result: Serum PSA levels ranged from 7.5 to 60 ng/ml. Half the patients had S. PSA in range 10-20 ng/ml (50%) followed by <10 ng/ml (32%) and >20 ng/ml (18%) respectively. Mean S. PSA levels were 17.25+14.01 ng/ml. p63 assessment was conclusive in 48 cases. Expression of p63 was seen in 20 (41.7%) cases only (Score 1 or above). Maximum number of cases showing p63 expression had score 1 (35.4%) followed by score 2 (n=2; 4.2%) and score 3 (2.1%) respectively. AMACR assessment was conclusive in 48 cases. Expression of AMACR was seen in 47/48 (97.9%) cases. Maximum had score 2+ (n=22; 45.8%) followed by Score 3+ (n=18; 37.5%), score 1+ (n=7; 14.6%) and score 0 (n=1; 2.1%) respectively. PTEN assessment was conclusive in 46 cases. There were 21 (45.7%) cases with score 0, 16 (34.8%) with score 1 and 9 (19.6%) with score 2. Conclusion: In present study, serum PSA levels of patients ranged from 7.5 to 60 ng/ml with half having S. PSA in 10-20 ng/ml range (50%). According to AJCC criteria, S. PSA levels <10 ng/ml are in general indicators of lower severity of prostate cancer while those in 10-20 ng/ml range indicate an intermediate severity of prostate cancer.